OPTIMASI MEDIA ALTERNATIF NUTRIENT AGAR BERBAHAN KACANG MERAH (Phaseolus vulgaris L.) DALAM MENUMBUHKAN Staphylococcus aureus - Mutiara Sulam, Nuri; Ilmi Sufa, Hafizah; Dermawan, Asep; Rismiati, Zuri (Jurnal Kesehatan Siliwangi, 2024)
Media are used to grow bacteria to diagnose infectious diseases, stock bacterial cultures, and in educational institutes for learning and research on the characteristic of bacteria. One of these media is nutrient agar which contains nutrients in the form of protein and carbohydrates. Growth media has less affordable prices so alternative media are created. Alternative media to replace nutrient agar with a vegetable protein source to replace the protein contained in the media. For example, the vegetable protein used is from red beans. Red beans contain protein and amino acids which will replace protein in nutrient agar media. This research aims to determine alternative media made from red beans that can be used as a substitute for nutrient agar, the optimum concentration and boiling time of red beans in growing Staphylococcus aureus with concentration variations of 5%, 10%, and 15% and time variations of 5 minutes, 10 minutes, and 15 minutes. In the research, inoculation was carried out using the pouring cup method. The results of the number of colonies on the alternative media will be compared with the results of the number of colonies on the control, namely nutrient agar. Based on the Generalized Linear Model (GLM) statistical test, an alternative media with a concentration of 10% and a boiling time of 10 minutes can be used as a substitute for nutrient agar.